Liquidity Management and Banks Financial Performance in Kuwait - Musaed Sulaiman AlAli (Financial Markets, Institutions and Risks)
Bank liquidity plays an important role in determining the bank’s financial performance. This study examines the impact of liquidity on the financial performance of ten Kuwaiti banks, whose shares are listed on the Kuwait Stock Exchange in the period 2010-2018. The article is based on the analysis of return on assets (ROA) and return on equity (ROE) as indicators of the bank’s financial efficiency in comparison with the five liquidity ratios. The results of the study showed a statistically significant direct relationship between ROA and the ratio of loans to total assets, the ratio of loans and deposits and the ratio of the financing deficit to total assets. According to the results of the calculations, a statistically significant inverse relationship between the ROA of liquid assets and the total assets and the ratio of liquid assets and deposits. The determination of return on equity (ROE) showed their statistically significant feedback only on liquid assets and deposits, while a significant direct relationship with the ratio of loans to total assets, the ratio of loans to deposits and the deficit of funding to the total assets. The results of this study provide an explanation of the contradictory results presented in the literature on the impact of liquidity on the financial results of banks. They found that the direction of the relationship depended on which financial ratio was used to explain the relationship (in this study, two ratios showed feedback, while the other three showed a direct ratio). The lack of a universal liquidity ratio will eventually lead to conflicting results.